A Low-Cost Tele-Imaging Platform for Developing Countries - Adambounou, Kokou; Adjenou, Victor; Salam, Alex P.; Farin, Fabien; N’Dakena, Koffi Gilbert; Gbeassor, Messanvi; Arbeille, Philippe (Frontiers in Public Health, 2014)
Purpose: To design a “low-cost” tele-imaging method allowing real-time tele-ultrasound expertise, delayed tele-ultrasound diagnosis, and tele-radiology between remote peripherals hospitals and clinics (patient centers) and university hospital centers (expert center). Materials and methods: A system of communication via internet (IP camera and remote access software) enabling transfer of ultrasound videos and images between two centers allows a real-time tele-radiology expertise in the presence of a junior sonographer or radiologist at the patient center. In the absence of a sonographer or radiologist at the patient center, a 3D reconstruction program allows a delayed tele-ultrasound diagnosis with images acquired by a lay operator (e.g., midwife, nurse, technician). The system was tested both with high and low bandwidth. The system can further accommodate non-ultrasound tele-radiology (conventional radiography, mammography, and computer tomography for example). The system was tested on 50 patients between CHR Tsevie in Togo (40 km from Lomé-Togo and 4500 km from Tours-France) and CHU Campus at Lomé and CHU Trousseau in Tours. Results: A real-time tele-expertise was successfully performed with a delay of approximately 1.5 s with an internet bandwidth of around 1 Mbps (IP Camera) and 512 kbps (remote access software). A delayed tele-ultrasound diagnosis was also performed with satisfactory results. The transmission of radiological images from the patient center to the expert center was of adequate quality. Delayed tele-ultrasound and tele-radiology was possible even in the presence of a low-bandwidth internet connection. Conclusion: This tele-imaging method, requiring nothing by readily available and inexpensive technology and equipment, offers a major opportunity for telemedicine in developing countries.